2022
DOI: 10.1002/ctm2.1046
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody‐mediated immunosuppression enables long‐term survival of transplanted human neural stem cells in mouse brain

Abstract: Background As the field of stem cell therapy advances, it is important to develop reliable methods to overcome host immune responses in animal models. This ensures survival of transplanted human stem cell grafts and enables predictive efficacy testing. Immunosuppressive drugs derived from clinical protocols are frequently used but are often inconsistent and associated with toxic side effects. Here, using a molecular imaging approach, we show that immunosuppression targeting costimulatory molecules CD4 and CD40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Therefore, we opted to perform our spatial transcriptomics analysis using the more effective IGF-I-expressing hNSC line with a view towards supporting future translational clinical trials implementing this cell line. We also demonstrated that injected hNSCs chiefly reside within the fimbria fornix and corpus callosum, but that a fraction migrates throughout the hippocampus, cortex, and other areas of the brain ( Mcginley et al, 2022 ).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Therefore, we opted to perform our spatial transcriptomics analysis using the more effective IGF-I-expressing hNSC line with a view towards supporting future translational clinical trials implementing this cell line. We also demonstrated that injected hNSCs chiefly reside within the fimbria fornix and corpus callosum, but that a fraction migrates throughout the hippocampus, cortex, and other areas of the brain ( Mcginley et al, 2022 ).…”
Section: Resultsmentioning
confidence: 82%
“…Representative fluorescence imaging (right panel; scale bar = 2 mm) shows GFP-labeled hNSCs disperse throughout the cortex following injection. Adapted from ( McGinley et al, 2022 ). (B) Latency to the hidden platform with training over days 1 to 9 and a visible (vis) positive control on day 10 in the Morris Water Maze test for WT (black), untreated 5XFAD (grey), vehicle injected 5XFAD (blue), and hNSC injected 5XFAD (red) mice; n = 7–10, * p < 0.05, by two-way ANOVA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transplanted NSCs have been reported to have long-term survival in vivo with the maintenance of multilineage differentiation, such as integration, synapse formation, and functional activity, and without tumorigenic growth in AD model mice [123]. The long-term survival of transplanted neural cells into the brain has been prolonged by immunosuppression of xenograft rejection in AD model mice [124]. Currently, many stem cell therapies have progressed well in clinical trials [33,125] by accumulating findings through basic research, including animal experiments.…”
Section: Conclusion 11mentioning
confidence: 99%